Influence of Socio-Economic Characteristics on The Use of Information Communication Technologies (Icts) in Income Generation Among Small Ruminants’ Farmers in Kaduna State - Kezi, D.M.; Ajala, M. K; Musa, M.W.; Ayuba, N.A. (The Nigerian Journal of Rural Extension and Development, 2023)
The study was carried out to determine income generation among small ruminant farmers in Kaduna State. The data for the study was obtained through use of structured questionnaires administered to 141 small ruminant farmers in Kudan, Ikara and Giwa local government areas ofKaduna State. The Local Government Areas were purposively selected due to their involvement in small ruminants’ production. Socio-economic characteristics of the small ruminants farmers were analyzed using descriptive statistics and the result showed that about 68% of the farmers were male with a mean age of 41 years and mean income of N33,534. Radio, television and mobile phone were the ICTs mostly used by farmers to source information. Regression analysis reveals that the factors which contributed significantly to income were household size and years of keeping small ruminants, while radio contributed negatively to the farmers’ income. It is recommended that extension workers should intensify information dissemination on rabbit’s production techniques to encourage farmers into production and marketing of rabbits. Funds should be provided for extension agencies to enable them air more radio and television programmes. Collaboration between agricultural extension agencies and education extension services should be established to promote adult education and computer education.